Household food insecurity is associated with depressive symptoms: Results from a Mexican population-based survey - Kolovos, S; Zavala, GA; Leijen, AS; Melgar-Quiñonez, H; van Tulder, M (Springer, 2020)
The objective of this cross-sectional study was to assess the relationship between food insecurity and depression in the Mexican population. We used data from the 2012 health and nutrition survey (ENSANUT), which is representative of the Mexican population. Food insecurity was determined by the Latin American and Caribbean Food Security Scale (ELCSA). Depressive symptoms were evaluated using the Center for Epidemiological Studies Depression Scale Short-Form (CES-D-SF). Adjusted logistic regression analyses and ANCOVA were used. Out of 33,011 participants, 5788 (18%) had high depressive symptoms and 24,098 (73%) experienced food insecurity. The adjusted logistic regression analysis showed that, participants with mild food insecurity, (OR = 1.47,95% CI = 1.27 to 1.71), moderate food insecurity (OR = 2.14,95% CI = 1.85 to 2.47) and severe food insecurity (OR = 3.01,95% CI = 2.51 to 3.60,) were more likely to have high depressive symptoms than food secure participants. Participants with moderate food insecurity (OR =1.45, 95% CI = 1.28 to 1.64) and severe food insecurity (OR =2.04, 95% CI = 1.76 to 2.37) were more likely to suffer from depression as compared to participants with mild food insecurity. Participants with severe food insecurity were more likely (OR=1.41, 95% CI = 1.21 to 1.65) to suffer from depression compared to participants with moderate food insecurity. This paper provides an overview of the complex problem of food insecurity and mental health. Despite the unknown causality, the analysis suggests a strong association between depression and food insecurity. This problem calls for much more attention from the scientific community. Given the high prevalence of depression and the high prevalence of household food insecurity in Mexico, the implementation of successful public health programs to improve food security is necessary.